Knowledge management applied to Digital Libraries: case study at Ministry of Health and Infraero - Miranda, Roberto Campos da Rocha; Teixeira, Sandra C; Filizola, Adriana R (Faculdade de Filosofia e Ciências, 2016)
Study shows the importance of using knowledge management approach in digital libraries context. Using two different government entities, Ministry of Health and Infraero - Brazilian Airports, both cases are treated under knowledge management principles, particularly measure of knowledge and socialization. The methodology applied involved two surveys in different groups: a survey to identify the existence of knowledge management parameters applied to the library employees and a survey to validate a digital library proposition applied to managers and decision makers. Results showed that knowledge management tools are not completely applied in libraries and there is a large worked field to be done, mainly in digital libraries.